Dental perspective on biomedical waste and mercury management: A knowledge, attitude, and practice survey - Ashima Garg Sood; Abhinav Sood (Wolters Kluwer Medknow Publications, 2011)
Context: Management of waste generated in any health-care facility is a critical issue as it poses a direct threat to human health as well as to the environment. The biomedical waste generated in the dental scenario includes sharps, used disposable items, infectious waste (blood-soaked cotton, gauze, etc.), hazardous waste (mercury, lead), and chemical waste (such as spent film developers, fixers, and disinfectants). A major concern in our field is management and disposal of mercury. Aims: To obtain information about the knowledge, attitude, and practices of dental institutions and dental practitioners in the disposal of waste. Settings and design: A self-administered questionnaire, composed of 50 questions was designed. Materials and Methods: The questionnaire was distributed among the participants, chosen randomly, including dental students, faculty from dental colleges and private practitioners in and around Delhi, India. Statistical analysis used: The percentage response for each question from all the participants was obtained and the data was calculated. Results: Many dentists have knowledge about the waste management but they lack in the attitude and practice. Conclusions: There is need for education regarding hazards associated with improper waste disposal at all levels of dental personnel. It is imperative that waste should be segregated and disposed off in a safe manner to protect the environment as well as human health.